Phenolic Composition of the Edible Parts (Flesh and Skin) of Bordo Grape (Vitis labrusca) Using HPLC-DAD-ESI-MS/MS - Lago-Vanzela, Ellen Silva [UNESP]; Da-Silva, Roberto [UNESP]; Gomes, Eleni [UNESP]; Garcia-Romero, Esteban; Hermosin-Gutierrez, Isidro (Amer Chemical Soc, 2011)
The aim of this study was the detailed characterization of the phenolic composition and the determination of the antioxidant activity of the Bora grape (Vitis labrusca) cultivated in South Brazil. The edible parts of Bora grapes (flesh and skin) contained 1130 mg/kg of total phenolic compounds (as gallic acid), mainly located in the skins. Anthocyanin content in the skins was high, largely as 3,5-diglucosides (1359 mg/kg, as malvidin 3,5-diglucoside). Total flavonols accounted for 154 mu mol/kg, mainly located in the skins and with myricetin 3-glucoside as the principal flavonol in both grape parts. Very low amounts of flavan-3-ol monomers and dimers and low amounts of polymeric proanthocyanidins, with a composition similar to that reported for V. vinifera grape varieties, were found in Bordo grape skins. Hydroxycinnamic acid derivatives mainly derived from caffeic acid and were found in the skins in high amounts, ten times higher than in the flesh (total amount: 483 mu mol/kg). Finally, the Bora grape cultivar can be considered a high resveratrol producer (10.91 mg/kg) and also exhibited a high value of total antioxidant capacity (37.6 +/- 1.0 mmol/kg, as Trolox).
Keywords: anthocyanins; flavonols; proanthocyanidins; hydroxycinnamic acid; resveratrol; Vitis labrusca; Bordo; Antioxidant capacity